Penerapan Akuntansi Pertanggung Jawaban Sebagai Alat Penilaian Kinerja (Studi Di Bagian Produksi PT. Pal Surabaya-Divisi Kapal Perang) - Moestika Setyaningrum, Rina; Darmawan, Farid (Jurnal Riset Ekonomi dan Bisnis, 2009)
Each company founded by one or a group of people basically aims to improve customer satisfaction. If customers feel satisfied, then the profit can be obtained automatically. To achieve this goal, management must make decisions quickly and appropriately. This situation requires top management to delegate authority along with a control system, supervision and performance assessment manager underneath. This can be achieved by applying the accounting liability.Battleship Division PT. PAL, the author has not seen the application of accounting responsibilities. Therefore, the authors try to discuss and interpret existing data on the production by comparing the realization of financing and budget irregularities known to have occurred. Through the accountability report of the Outfitting Department, Ministry of Construction and the Ministry of Production Support, management can measure the effective and efficient production costs in the company. Thus, the company will have no difficulty in determining which of many costs that would affect the decision-making and increase overall company performance.Keywords: Accountability Accounting, Implementation, Reporting, Management Accounting, Comparative Descriptive